An introduction to contemporary history - Barraclough, Geoffrey (Basic Books, 1965)
This books introduce about nature of contemporary, impact of technical and scientific advance, dwarfing of Europe, from the European balance of power, from individualism to mass democracy, the revolt against the west, the ideological challenge, art and literature in the contemporary world.